Trends in premature cerebrovascular disease mortality in the Polish population aged 25-64 years, 2000-2016 - Alicja Cicha-Mikołajczyk; Aleksandra Piwońska; Witold Śmigielski; Wojciech Drygas (National Institute of Public Health - National Institute of Hygiene, 2022)
Background. Many scientific reports have shown a decrease in total cerebrovascular disease (CeVD) mortality over the past few decades, but too little attention has been paid to premature mortality. CeVD accounted for 22.5% and 17.8% of premature cardiovascular disease deaths in Poland, in 2000 and 2016, respectively. Objective. The aim of the study was to analyse premature CeVD mortality in the Polish population in the recent years, the dynamics of its changes and the potential factors that may have contributed to the decline in mortality. The main goal of the study was to overview the levels and trends in premature CeVD mortality with an emphasis on haemorrhagic, ischaemic and unspecified (not specified as haemorrhagic or ischaemic) stroke. Material and methods. The analysis was based on a database of the Central Statistical Office of Poland and included data from 2000-2016 on premature cerebrovascular deaths occurring between 25 and 64 years of age (N=104,786). CeVD and haemorrhagic, ischaemic or unspecified stroke were coded with ICD-10 codes I60-I69, I61-I62, I63 and I64, respectively. The analysis included assessment of CeVD deaths distribution and evaluation of age-specific mortality rates in 10-year age groups and age-standardised mortality rates (SMR) in the age group 25-64 years, separately for men and women. Trends in SMRs have been studied in the period 2000-2016. Results. The number of CeVD deaths decreased by 32.8% in men and 48.8% in women. There was a two-fold decline in CeVD mortality: from 59 to 29 male and from 30 to 12 female per 100,000. In addition, a 2-year increase in the median age of CeVD death was observed (Men: 56.4 to 58.4 years, Women: 56.4 to 58.7 years, p<0.001). A statistically significant decline in mortality (per 100,000) was also noticed for haemorrhagic stroke (Men: 18.7 to 10.4; Women: 9.6 to 3.8), ischaemic stroke (Men: 11.8 to 8.4; Women: 4.7 to 3.0) and unspecified stroke (Men: 19.7 to 3.5; Women: 9.1 to 1.3). Conclusions. A substantial decline in premature CeVD mortality was observed in the period 2000-2016. Additionally, the number of deaths that could not be classified as haemorrhagic or ischaemic stroke death decreased significantly. The increasingly widespread use of new post-stroke therapies and their availability make it possible to expect a further decrease in CeVD mortality. However, the necessary actions should be taken to compensate for the disparities in CeVD mortality between men and women.